Design and Implementation of Computer Programs for Analysis and Detection of Spatial Deformation - Setan, Halim (Fakulti Ukur dan Harta Tanah, 1995)
This paper summarised the strategy developed for geometrical detection of spatial deformation using geodetic method. This developed strategy has been implemented in five computer programs (ESTIMATE, COMPS, COMON, DETECT AND ROBUST). The test results are also presented.